Optical, Electrochemical, Third-Order Nonlinear Optical Investigations of 3,4,5-Trimethoxy Phenyl Substituted Non-Aqueous Phthalocyanines - Srivishnu, K. S.; Banerjee, Dipanjan; Ramnagar, Ramya Athira; Rathod, Jagannath; Giribabu, Lingamallu; Soma, Venugopal Rao (Frontiers in Chemistry, 2021)
A new series of non-aqueous phthalocyanines having 3,4,5-trimethoxy phenyl group at peripheral positions in which the central cavity possessing Cu(II), Zn(II) and without metal has been synthesized and its absorption, fluorescence (steady-state and excited state lifetimes), electrochemical, and third-order nonlinear optical (NLO) properties were evaluated. Absorption studies data suggest that all three phthalocyanines obey Beer-Lambert’s law and redox properties indicate that both oxidation and reduction reactions are macrocyclic centered. The singlet quantum yields were measured in different solvents and were found to be in the range of 0.2 to 0.5 in case of free-base whereas it was in the range of 0.1 to 0.5 in zinc derivative, while the time-resolved fluorescence data revealed lifetimes of typically a few ns. The third-order NLO properties were investigated using the Z-scan technique with kilohertz (for retrieving true electronic nonlinearities) and megahertz repetition rate femtosecond pulses at 800 nm. Intensity-dependent Z-scan studies revealed robust NLO coefficients for solutions and thin films (two-photon absorption cross-sections of 9300-57000 GM) of these molecules suggesting a strong potential for optical switching, imaging, and optical limiting applications.